Governance challenges and non-traditional security threats in Pakistan: terrorism, cybersecurity, and climate risks - Muhammad Bahar Khan; Muhammad Khalid Anser; Imran Naseem; Alamzeb Aamir; Khalid Zaman (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
Pakistan’s security concerns have expanded to include terrorism, cyber insecurity, and climate-induced risks. These interconnected concerns are straining governance, institutional coordination, and long-term stability, necessitating a comprehensive reevaluation of national security beyond military solutions. The study analyses Pakistan’s non-traditional security threats over time, evaluates institutions and governance’s responses to cyber threats, climate change, and terrorism, and identifies policy gaps that hinder integrated security management. Systematic document analysis underpins the study’s qualitative research design. Official papers, anti-terrorism initiatives, cybersecurity frameworks, climate change adaptation measures, and scientific studies from 2001–2024 provided information. The study uses thematic and comparative methodologies to track risks, institutional responses, and governance effectiveness across sectors. The Result show Three significant patterns emerge. First, even while counterterrorism efforts have considerably reduced militant violence, governance issues, including social and economic marginalization and ideological radicalization, have not been addressed. Second, as Pakistan’s digital dependence has outpaced institutional cybersecurity safeguards, regulatory monitoring and policy responses are lacking. Third, climate-related hazards, including water stress and extreme weather events, aggravate food insecurity and rural livelihoods, increasing social and security vulnerabilities. The lack of policy integration and interagency coordination limits long-term effectiveness across the board. The study’s results and policy implications suggest that integrated governance is needed to address Pakistan’s security issues, rather than sector-specific initiatives. Policy implications include improving institutional coordination, integrating climate resilience and cybersecurity into national security planning, and implementing inclusive governance reforms to promote community resilience. A flexible and comprehensive plan is needed to improve national stability and sustainable growth.